Amphiphilic sodium alginate-polylysine hydrogel with high antibacterial efficiency in a wide pH range. (1st January 2023) - Jin, Fangyu; Liao, Shiqin; Li, Wei; Jiang, Chenyu; Wei, Qufu; Xia, Xin; Wang, Qingqing
Abstract: Bacterial infection is a major pathological factor leading to persistent wounds. With the aging of population, wound infection has gradually become a global health-issue. The wound site environment is complicated, and the pH changes dynamically during healing. Therefore, there is an urgent need for new antibacterial materials that can adapt to a wide pH range. To achieve this goal, we developed a thymol-oligomeric tannic acid/amphiphilic sodium alginate-polylysine hydrogel film, which exhibited excellent antibacterial efficacy in the pH range from 4 to 9, achieving the highest achievable 99.993 % (4.2 log units) and 99.62 % (2.4 log units) against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli, respectively. The hydrogel films exhibited excellent cytocompatibility, suggesting that the materials are promising as a novel wound healing material without the concern of biosafety. Graphical abstract: Unlabelled Image